Development of intellectual skills in teachers of basic education in Machala, Ecuador - Espinoza Freire, Eudaldo Enrique (2019)
The general intellectual abilities constitute the premises for the formation of professional abilities and competences; however, there are shortcomings in its implementation since basic education. This study was carried out with the objective of characterizing the development process of these skills in the students of the basic schools of Machala. The methodological strategy responded to the quantitative-qualitative paradigm, systematized through the methods of scientific observation, phenomenological, hermeneutic and statistical; the information collected through the application of the observation guide to 12 classes and the interview with 40 randomly selected teachers were summarized through tables and statistical figures. The findings allowed concluding that there are limitations in the intentionality of the development of general intellectual abilities.